Nitrogen reduction in basal fertilization enhances soil physicochemical properties and reshapes microbial community structure to alleviate tobacco bacterial wilt - Shi, Chaojun; Yang, Xiufang; Gao, Zhengfeng; Liu, Yao; Yan, Yuqiu; Chen, Lijie; Jiang, Jinhui; Zhang, Honglin; Yang, Neng; Wang, Jindan; Zhou, Yinbiao; Jia, Jiahao; et al. (Frontiers in Microbiology, 2026)
IntroductionBacterial wilt caused by Ralstonia solanacearum is a devastating soil-borne disease that seriously threatens tobacco yield and quality worldwide. Excessive nitrogen fertilization has been widely implicated in soil microecological imbalance and increased disease incidence; however, the regulatory mechanisms underlying nitrogen reduction remain poorly understood.MethodsHere, a randomized block field experiment was conducted with four basal nitrogen application levels, including conventional fertilization and 10%, 20%, and 30% nitrogen reduction. Disease incidence, rhizosphere soil physicochemical properties, enzyme activities, and microbial community structure were systematically assessed using biochemical analyses and high-throughput sequencing.ResultsThe results showed that moderate nitrogen reduction significantly decreased the rhizosphere abundance of R. solanacearum, leading to a marked reduction in disease incidence and severity. With decreasing nitrogen input, soil pH increased, while moderate nitrogen reduction significantly enhanced available nitrogen, phosphorus, and potassium, microbial biomass carbon and phosphorus, and optimized the activities of urease, acid phosphatase, nitrate reductase, and nitrite reductase. Microbial community analysis revealed that nitrogen reduction reshaped community structure, increased α-diversity, and enriched beneficial genera such as Arthrobacter and Amycolatopsis. Redundancy analysis further identified soil pH, microbial biomass carbon, acid phosphatase activity, and soil organic matter as the primary drivers of microbial community shifts.DiscussionOverall, these findings demonstrate that moderate reduction of basal nitrogen fertilization effectively suppresses tobacco bacterial wilt by improving rhizosphere soil properties and steering microbial community assembly toward a disease-suppressive state. This study provides both a theoretical basis and practical guidance for sustainable tobacco disease management and nitrogen reduction strategies.